Repossession and the Democratization of Credit - Assunção, Juliano J.; Benmelech, Efraim; Silva, Fernando S. S. (Review of Financial Studies, 2014)
We exploit a 2004 credit reform in Brazil that simplified the sale of repossessed cars used as collateral for auto loans. We show that the reform expanded credit to riskier, self-employed borrowers who purchased newer, more expensive cars. The legal change has led to larger loans with lower spreads and longer maturities. Although the credit reform improved riskier borrowers' access to credit, it also led to increased incidences of delinquency and default. Our results shed light on the consequences of a credit reform and highlight the crucial role that collateral and repossession play in the liberalization and democratization of credit.